Evaluation of the Effectiveness of Immunosorbent-Based Hemosorption in Comprehensive Conservative Therapy of End-Stage Heart Failure Patients - Denysiuk, Kateryna V.; Loskutov, Oleh A.; Druzhyna, Oleksandr M. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Background. Heart failure is the leading cause of death among all cardiovascular diseases. The five-year survival rate in such patients is 50%. In most cases, heart transplantation is the treatment of choice in these patients. However, its use is limited by severe and progressive donor organ deficiency. The aim. To study the effectiveness of immunosorbent-based hemosorption in comprehensive conservative treatment of patients with end-stage heart failure. Materials and methods. A retrospective analysis of the results of treatment in 59 patients 90% men, 10% women; mean age 41.3 ± 12.4 years; NYHA IIB-III, baseline left ventricular ejection fraction 21.1 ± 4.66%, left ventricular endsystolic volume 206.87 ± 84.1 ml, left ventricular end-diastolic volume 264.4 ± 86.02 ml) hospitalized for end-stage heart failure was performed. Conservative therapy was carried out following international guidelines and was supplemented by a course of 2-4 hemosorption procedures for which hemosorbent granulated deliganding was used. The Student’s t-test was used to analyze the data. Results. The clinical condition of all patients improved after the performed hemosorption procedures by at least one NYHA class. The brain natriuretic peptide level decreased from 1281.17±165.33 pg/ml to 859.48±113.38 pg/ml (p<0.05). Left ventricular ejection fraction increased by 10.77±4.3% (to 29.36 ± 6.27%) (p<0.01), and after 12 months it was 34 ± 2.59% (p<0.05). Left ventricular end-systolic volume decreased by 68.75±43.56 ml (to 137.77 ± 33.21 ml), left ventricular end-diastolic volume decreased by 41.38±31.48 ml (to 238.04 ± 82.1 ml) (p<0.05). Conclusions. The use of hemosorption with hemosorbent granulated deliganding, against the background of conservative treatment of end-stage heart failure, improves the contractile function of the heart and general clinical condition of patients.